A breakthrough in research on depression screening: from validation to efficacy studies - Costantini, Luigi; Costanza, Alessandra; Odone, Anna; Aguglia, Andrea; Escelsior, Andrea; Serafini, Gianluca; Amore, Mario; Amerio, Andrea (Acta Biomedica Atenei Parmensis, 2021)
In the last two decades the awareness of depression as a public health issue has increased and the literature has flourished towards its primary and secondary prevention. Whereas timely targeting of depression risk factors is a frontier towards reducing the incidence of the disorder, nowadays the early diagnosis is of primary importance. Screening depressive disorders is paramount, since there are several types of depression. Besides, early diagnosis would improve the outcome of treatment, reduce the frequency of relapses and generally lead to higher levels of quality of life. We highlight the feasibility of depression screening in primary care and the need of a comprehensive public health approach.